PERTUMBUHAN DAN PRODUKSI JAGUNG PULUT LOKAL SULAWESI SELATAN YANG DITANAM DI POLIBAG PADA BERBAGAI KOMBINASI PERLAKUAN PUPUK ORGANIK - Juhaeti, Titi; Hidayati, N; Rahmansyah, M (Perhimpunan Biologi Indonesia, 2013)
Research has been carried out through the utilization of organic fertilizer to improve the productivity of local maizecultivar originated from South Sulawesi. The study was conducted at the research station of Research Center for Biology,Cibinong Science Center. Corn seed were planted in polybag containing mixture of soil and compost, 6 and 2kg, respectively. The research were carried out by Randomized Complete Block Design arranged in factorial experimentwith four replications. The first factors are three types of local maize namely A: rice corn (pulut beras, BataraKoasa), B: waxy corn (pulut biji, Batara Kamu), C: pulut hibrida (hybrid cultivar). The second factors are 14 combinationtreatment as a mixture of LIPI organic fertilizer (Beyonic-StarTmik, Bio121, EM-121 and MegaRhizo) andanorganic NPK fertilizer. The variables observed were plant growth and production. The results showed that thehybrid cultivar had higher total corn yield productivity compared to the local one, although hybrid cultivar hassmaller plant biomass. Waxy corn (B) accession showed the weight, length and diameter of cob, and also the weightof 100 grains larger than rice corn (A). Fertilization treatments significantly affect the corn-cob productivity which isincludes the weight, length, and diameter units. Fertilization treatments such as EM-121 + (½ dose of NPK), BIO-121 + (½ dose of NPK), and Beyonic + (¼ dose of NPK) showed a good effect on plant, and it was not significantlydifferent with 100% NPK (full doses of NPK). The three corn cultivar showed different responses to fertilizationtreatments.Keywords: local corn, biofertilizer, growth, production